2013
DOI: 10.1103/physrevb.88.064403
|View full text |Cite
|
Sign up to set email alerts
|

Spin pumping and inverse spin Hall effect in germanium

Abstract: We have measured the inverse spin Hall effect (ISHE) in n-Ge at room temperature. The spin current in germanium was generated by spin pumping from a CoFeB/MgO magnetic tunnel junction in order to prevent the impedance mismatch issue. A clear electromotive force was measured in Ge at the ferromagnetic resonance of CoFeB. The same study was then carried out on several test samples, in particular we have investigated the influence of the MgO tunnel barrier and sample annealing on the ISHE signal. First, the refer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 55 publications
7
55
0
Order By: Relevance
“…1 Indeed, SP effect driven by its versatility is being widely explored to determine spin to charge current conversion efficiency, referred as spin Hall angle (SH), in various kind of materials ranging from strong spin-orbit coupling system of heavy metals [2][3] , conventional semiconductors like (Si and Ge) [4][5] , wide-band gap semiconductor oxides (ZnO, ITO) [6][7] to ferromagnetic metallic alloys 3,8 oxides like SrRuO3 9 and even organic polymers 10 . In practice, other techniques of non-local injection in lateral spin valve structure 11 , spin-torque ferromagnetic resonance [12][13][14] and time-resolved magneto-optical Kerr effect 15 have also been established by various groups to measure SH of different materials.…”
Section: ___________________________ A)mentioning
confidence: 99%
“…1 Indeed, SP effect driven by its versatility is being widely explored to determine spin to charge current conversion efficiency, referred as spin Hall angle (SH), in various kind of materials ranging from strong spin-orbit coupling system of heavy metals [2][3] , conventional semiconductors like (Si and Ge) [4][5] , wide-band gap semiconductor oxides (ZnO, ITO) [6][7] to ferromagnetic metallic alloys 3,8 oxides like SrRuO3 9 and even organic polymers 10 . In practice, other techniques of non-local injection in lateral spin valve structure 11 , spin-torque ferromagnetic resonance [12][13][14] and time-resolved magneto-optical Kerr effect 15 have also been established by various groups to measure SH of different materials.…”
Section: ___________________________ A)mentioning
confidence: 99%
“…Because the spin pumping relies only on the spin dynamics and thus enables a charge-free spin injection [14], by now it is widely used as a versatile spin injection method. Indeed, the target materials range from normal metals [15][16][17][18][19][20][21][22], semiconductors [14,[23][24][25], magnetic metals [26][27][28], and insulators [29], to more exotic systems such as graphene [30,31], organic materials [32,33], a topological insulator [34], and a Rashba system [35]. Given this background, it is worth investigating and clarifying the nature of spin pumping into superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Spin transport has been reported through a Ni/Ge/AlGaAs junction; however, optical spin injection lacks the scalability needed for nanoelectronic applications [17]. Some electrical studies [18][19][20] reported spin injection into highly doped n-Ge at room temperature (RT), raising the possibility that RT Ge spintronics can be realized. Unfortunately, these studies used a three-terminal method, the reliability of which is now being called into question.…”
mentioning
confidence: 99%